2013
DOI: 10.1093/mnras/stt1993
|View full text |Cite
|
Sign up to set email alerts
|

Helium enhanced stars and multiple populations along the horizontal branch of NGC 2808: direct spectroscopic measurements★

Abstract: We present an abundance analysis of 96 horizontal branch (HB) stars in NGC 2808, a globular cluster exhibiting a complex multiple stellar population pattern. These stars are distributed in different portions of the HB and cover a wide range of temperature. By studying the chemical abundances of this sample, we explore the connection between HB morphology and the chemical enrichment history of multiple stellar populations. For stars lying on the red HB, we use GIRAFFE and UVES spectra to determine Na, Mg, Si, C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
154
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(170 citation statements)
references
References 105 publications
15
154
1
Order By: Relevance
“…More-massive stars in the first generation, having experienced the advanced phases of stellar nucleosynthesis, burn hydrogen via the CNO cycles. The degree of mixing between first-generation ejecta and pristine cluster gas determines whether the second generations are 'extreme' population stars (sometimes formed from pure ejecta) or belong to the 'intermediate' population that give rise to the observed anticorrelations (mixed ejecta and cluster gas, see Carretta et al 2009 Marino et al 2014 and is consistent with observed split main sequences (Piotto et al 2007;Milone et al 2012). …”
Section: Mass and 4 He-enhancementsupporting
confidence: 57%
“…More-massive stars in the first generation, having experienced the advanced phases of stellar nucleosynthesis, burn hydrogen via the CNO cycles. The degree of mixing between first-generation ejecta and pristine cluster gas determines whether the second generations are 'extreme' population stars (sometimes formed from pure ejecta) or belong to the 'intermediate' population that give rise to the observed anticorrelations (mixed ejecta and cluster gas, see Carretta et al 2009 Marino et al 2014 and is consistent with observed split main sequences (Piotto et al 2007;Milone et al 2012). …”
Section: Mass and 4 He-enhancementsupporting
confidence: 57%
“…Blue HB stars cooler than the Grundahl-jump are (moderately) O-poor and Na-rich. These results have been confirmed by Marino et al (2014) using higher signal-to-noise ratio (S/N) spectra, from which they also derived He abundances and finding quite a high value of Y ∼ 0.34 ± 0.01 ± 0.05 for BHB stars. Even He-richer stars should be present, but they should be hotter than the Grundahl-jump (D'Antona et al 2005), so this cannot be verified directly.…”
Section: Introductionsupporting
confidence: 54%
“…We derived He abundances for M 22 stars using these relations (Col. 2 of Table 6, with errors on the next column), and found an average He abundances by mass of Y = 0.338±0.014± 0.05, where the first error bar is derived from star-to-star scatter, and the second one referring to systematics is simply the one adopted by Marino et al (2014) ΔY ∼ 0.015 : Sweigart 1987). This indicates that the BHB stars of M 22 hotter than 9000 K are moderately He-rich.…”
Section: Helium Abundancesmentioning
confidence: 85%
See 1 more Smart Citation
“…Dependence of the initial helium spread on the polluter scenario Despite the many differences between the scenarios that have been developed to explain the abundance properties of GCs, it is widely accepted that the Na-enriched (2P) GC stars have started their life with a higher helium content than their 1P counterparts (this is actually obvious as helium is the main product of hydrogen burning). This has been confirmed by direct spectroscopic measurements of non-local thermodynamic equilibrium He abundances for a subset of blue horizontal branch stars in one GC (NGC 2808;Marino et al 2014). However the initial helium distribution among 2P stars is not well known yet, as predictions for the extent of helium enrichment along the sodium distribution in 2P stars strongly depend on the nature of the invoked 1P polluters.…”
Section: The Importance Of Quantifying Helium Variationsmentioning
confidence: 73%